Ultrawide Spectrum Metallic Plane Blackbody with Extremely High Absorption from 0.2 to 25 µm - Jin‐Yong Qi; Xue‐Qing Liu; Zi‐Jian Liu; Xin Zhang; Chao Li; Qi‐Dai Chen; Lei Wang; Hong‐Bo Sun (Advanced Science)
Abstract A plane blackbody serves as a standard radiation source, providing a precise quantitative relationship between input radiation and the output of infrared detectors, which is essential component of space infrared remote sensing instruments. However, current plane blackbodies fabricated by coating or surface structuring are unable to achieve uniform and stable high absorption in the ultrawide spectral range spanning the UV‐VIS‐NIR‐MIR. Here, a femtosecond laser “V”‐ scanning method is proposed for the fabrication of cross‐scale multi‐layered micro‐ and nanocomposite structures on copper surfaces to realize ultrawide spectrum metallic plane blackbody with high absorption. The structures consist of a micrometer cone‐tip structure with a depth‐to‐width ratio of 7:1 (period 30 µm, depth 210 µm), an oxide layer with a thickness of more than 2 µm, and nanoparticles of different sizes, achieving uniform high absorption rates exceeding 99% in the localized spectral range of 400–700 nm and over 98% from the UV to MIR range of 200 nm to 25 µm. This strategy offers a generalized approach to enhance surface light absorption, with significant application potential in infrared calibration, passive radiation cooling, and stray light suppression.